Comer y ser : raíces gastronómicas de México - Armella, Nathalie; Camacho, Vicente; Franch, Paulina; Villanueva, Carlos (Curator); Galería Andrea Pozzo; Museo de Historia Mexicana (Monterrey, Mexico) (Mexico, D.F. : CACCIANI, S.A. de C.V. : Fundacion Cultural Armella Spitalier, 2012)
Reflections on pre-Hispanic roots of Mexican cuisine, illustrated with numerous photographs of codices, earthenware vessels, local produce, cooking instruments, and ingredients. Includes essays on rites and offering, crop cultivation, commerce and trade, variety of foods, types of meals, and relationship between food and death.
Published in connection with the exhibition held Jan. 27-May 31, 2011 at the Galería Andrea Pozzo at the Universidad Iberoamericana and Nov. 23, 2011-Mar. 25, 2012 at the Museo de Historia Mexicana in Monterrey, Mexico.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed January 5, 2017)
Keywords: Cooking -- Mexico -- History; Food habits -- Mexico -- Exhibitions; Food habits -- Mexico -- History; Gastronomy -- Mexico -- Exhibitions; Indians of Mexico -- Food -- Exhibitions; Mexico -- Antiquities -- Exhibitions; Mexico -- Social life and customs -- History; Electronic books